Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fncom.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Circuit Hypothesis for the Pathogenesis of Blepharospasm

Abstract: Blepharospasm (sometimes called “benign essential blepharospasm,” BEB) is one of the most common focal dystonias. It involves involuntary eyelid spasms, eye closure, and increased blinking. Despite the success of botulinum toxin injections and, in some cases, pharmacologic or surgical interventions, BEB treatments are not completely efficacious and only symptomatic. We could develop principled strategies for preventing and reversing the disease if we knew the pathogenesis of primary BEB. The objective of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…The most common symptoms reported by patients were difficulty opening the eyes due to persistent photophobia and/or ocular pain, suggesting that blepharospasm is associated with sensory-motor disintegration. [15][16][17] Although it is difficult to conclude whether the motor system or sensory system is primarily involved in the mechanism of blepharospasm, our other study 18 based on patients' statement indicates that a number of patients with drug-induced blepharospasm primarily or predominantly realise sensory disturbance such as photophobia and ocular or periocular pain/irritation. This results are compatible to the hypothesis in focal dystonia that abnormal processing of the somatosensory input in the central nervous system induces insufficient sensorimotor integration.…”
Section: Discussionmentioning
confidence: 80%
“…The most common symptoms reported by patients were difficulty opening the eyes due to persistent photophobia and/or ocular pain, suggesting that blepharospasm is associated with sensory-motor disintegration. [15][16][17] Although it is difficult to conclude whether the motor system or sensory system is primarily involved in the mechanism of blepharospasm, our other study 18 based on patients' statement indicates that a number of patients with drug-induced blepharospasm primarily or predominantly realise sensory disturbance such as photophobia and ocular or periocular pain/irritation. This results are compatible to the hypothesis in focal dystonia that abnormal processing of the somatosensory input in the central nervous system induces insufficient sensorimotor integration.…”
Section: Discussionmentioning
confidence: 80%
“…We use a phase-based undirected connectivity measurement and inspect graph metric changes at a single snapshot of the available parameters within the dynamic modularity framework we applied. This initial implementation of a graph theoretical approach on human neurostimulation effects may be expanded in the future to investigate the directed communication between these resonating communities (e.g., Reimann et al, 2017 ), cross-frequency communication (Canolty & Knight, 2010 ), and increased resolution across frequencies of the brain. The methodological choices within this work also focused on merely one spatiotemporal scale, which may not completely account for the spectral sensitivity across the regions of the brain, and the results target a wakeful resting state in individuals, and it may not extend to the active or sleeping brain (Hasson, Nusbaum, & Small, 2009 ; Massimini et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other environmental factors, including dry eyes, greater exposure to sunlight and photophobia [41][42][43] may then trigger the clinical manifestations of BSP. In this regard, it has recently been suggested that greater exposure to sunlight may induce an increase in orbicularis oculi muscle drive, which is an adaptive process in healthy subjects but may turn into a maladaptive mechanism in subjects predisposed to BSP [44]. Other factors that affect blinking are the level of dopamine in the central nervous system and aging.…”
Section: Issn 2637-6997mentioning
confidence: 99%